Blockchain technology in supply chain operations: Applications, challenges and research opportunities. (October 2020) - Dutta, Pankaj; Choi, Tsan-Ming; Somani, Surabhi; Butala, Richa
Highlights: Evaluate 178 research articles in the field of blockchain implementation in supply chains. Identify the current trends of research on blockchain in different domains of supply chain operations. Examine various supply chain functions that can be enhanced through blockchain technology. Present strong excerpts of blockchain applications in supply chains across various industrial sectors. Suggest managerial implications, highlight challenges and build a future research agenda. Abstract: Blockchain is a technology with unique combination of features such as decentralized structure, distributed notes and storage mechanism, consensus algorithm, smart contracting, and asymmetric encryption to ensure network security, transparency and visibility. Blockchain has immense potential to transform supply chain (SC) functions, from SC provenance, business process reengineering to security enhancement. More and more studies exploring the use of blockchain in SCs have appeared in recent years. In this paper, we consider a total of 178 articles and examine all the relevant research done in the field associated with the use of blockchain integration in SC operations. We highlight the corresponding opportunities, possible societal impacts, current state-of-the-art technologies along with major trends and challenges. We examine several industrial sectors such as shipping, manufacturing, automotive, aviation, finance, technology, energy, healthcare, agriculture and food, e-commerce, and education among others that can be successfully revamped with blockchain based technologies through enhanced visibility and business process management. A future research agenda is established which lays the solid foundation for further studies on this important emerging research area.